Application of yeast in plant-derived aroma formation from cigar filler leaves - Yao, Lan; Huang, Chenyi; Ding, Jingyi; Zhang, Tongtong; Yu, Jun; Yang, Chunlei; Chen, Xiong (Frontiers in Bioengineering and Biotechnology, 2022)
There are various degrees of defects of cigar filler leaves after air drying. In order to improve the quality and plant-derived aroma content of cigar filler leaves, nine aroma-producing yeasts were applied in artificially solid-state fermentation of cigar filler leaves in this study. The differences with various yeasts application were compared by chemical composition and GC-MS analysis. The results showed that 120 volatile components were identified and quantified in cigar filler leaves after fermentation, including aldehydes (25 types), alcohols (24 types), ketones (20 types), esters (11 types), hydrocarbons (13 types), acids (4 types) and other substances (23 types). Based on the analysis of odor activity value (OAV), the OVA of fruity and floral aroma components were higher. It was found that floral aroma are the representative aroma types of cigar filler leaves treated with Clavispora lusitaniae, Cyberlindera fabianii, Saccharomycosis fibuligera and Zygosaccharomyces bailii R6. After being inoculated with Hanseniaspora uvarum J1, Hanseniaspora uvarum J4 and Pichia pastoris P3, the OAV of fruity aroma in cigar filler leaves was the highest, followed by tobacco aroma and woody aroma. The correlation between volatile components of cigar filler leaves with different yeasts was revealed after PCA analysis. It was concluded that the quality of cigar filler leaves was improved, and cigar filler leaves fermented with different yeasts showed different flavor.